Targeting the complexity of Src signalling in the tumour microenvironment of pancreatic cancer: from mechanism to therapy. (5th August 2019) - Parkin, Ashleigh; Man, Jennifer; Timpson, Paul; Pajic, Marina
Abstract : Pancreatic cancer, a disease with extremely poor prognosis, has been notoriously resistant to virtually all forms of treatment. The dynamic crosstalk that occurs between tumour cells and the surrounding stroma, frequently mediated by intricate Src/FAK signalling, is increasingly recognised as a key player in pancreatic tumourigenesis, disease progression and therapeutic resistance. These important cues are fundamental for defining the invasive potential of pancreatic tumours, and several components of the Src and downstream effector signalling have been proposed as potent anticancer therapeutic targets. Consequently, numerous agents that block this complex network are being extensively investigated as potential antiinvasive and antimetastatic therapeutic agents for this disease. In this review, we will discuss the latest evidence of Src signalling in PDAC progression, fibrotic response and resistance to therapy. We will examine future opportunities for the development and implementation of more effective combination regimens, targeting key components of the oncogenic Src signalling axis, and in the context of a precision medicine‐guided approach. Abstract : The Src signalling cascade has been recognised as a key driver of pancreatic tumourigenesis, disease progression and therapeutic resistance, and plays an important role in mediating the dynamic crosstalk that occurs between tumour cells and their surrounding microenvironment. Consequently, numerous agents have been developed to block this complex network, and this review will examine their potential as well as discuss future opportunities for improvement.